Conducting the reference interview : - Ross, Catherine Sheldrick (Neal-Schuman Publishers Inc., 2009)
Teaches you to understand the needs of public, academic and special library users across different virtual settings - email, text messaging, and social networking websites - as well as in traditional and face-to-face models of communication. This book includes exercises and examples to help you practice effective reference transactions.